Law Enforcement of Single Traffic Accidents Causing Death and Injury of Passengers - Zapetri, Novita; Amiq, Bachrul; Prawesti, Wahyu (Justice Voice, 2023)
The high number of accidents in Indonesia is one of the impacts of the lack of awareness of road users and road transportation providers in maintaining traffic order and road transportation security. Services that are safe, secure, orderly, smooth, and integrated with other modes of transportation can boost the national economy, advance public welfare, strengthen national unity, and be able to uphold the dignity of the nation. This study aims to analyze law enforcement by police officers in single traffic accidents that cause passengers to die and the responsibilities of drivers and the Otobus Company (PO) to victims. The method uses normative legal research with a statutory approach and the concept of law enforcement. The research shows that the maximum punishment imposed on the perpetrators of traffic crimes normatively can be explained by the relatively low maximum punishment ranging from one year to five years and until now the legal basis for capturing the perpetrators of traffic crimes still depends on the Criminal Code inherited from the Dutch Colonial Government. Law enforcement by police officers with the investigation and investigation of criminal cases in the case of a single accident experienced by the suspect on the toll road ensnares the Road Traffic and Transportation Law (LLAJ Law). Drivers and POs are responsible for victims by providing compensation to accident victims following the LLAJ Law by not removing or reducing criminal liability.